'Go Tell the Spartans, Passerby': Whom to Remember Ahead of Whom?. Issue 5 (17th October 2022) - Stemplowska, Zofia
ABSTRACT: The dead are among us. We are reminded of their names through the books we read, the hoovers we buy, the sandwiches we consume, the tarmac we travel on, the wellingtons we wear, or, frequently, the buildings we visit. Even if we settled on the criteria for being worthy of commemoration, what should we do about the fact that there seem to be so many people who would likely meet them? Commemoration is a form of attention giving, and attention is a scarce resource. It is scarce even if it could be permissibly commanded at will. It is even more scarce when commanding attention may violate someone's freedom to decide for themselves where to bestow it. I will argue that when it comes to public commemorative attention, there are duties that fall on us all to remember the now dead victims of injustice. I will also offer reasons for why such duties would normally mean that we need to prioritize the remembrance of the victims of injustice ahead of remembrance that might be owed to those who had expectations of being remembered or even took steps by donations to secure such remembrance.